Pergumulan Rule of Law dan Politik Kapitalisme dalam Konteks Keindonesian - Zaenurrosyid, Ahmad (Jurnal Review Politik, 2016)
Law, economic have one vision, happiness for human being. We found the existence of inequality in the dynamic economy of Indonesia. This is a crucial problem for sosio-economy productivity. In this writing, Marxism theory about the class and conflict is applied to analyze in Indonesia context. Neo-liberlisme become an ideology of capitalist as legitimation supported by international institution, such as World Bank, IMF,etc. Rule of law in term of dynamic regulation in Indonesia is as a part of alternative solution to control a socio-economic equality supported by progresif law in contemporary era.